Efficacy of antimicrobial solutions against polymicrobial root canal biofilm. (14th January 2016) - Ruiz‐Linares, M.; Aguado‐Pérez, B.; Baca, P.; Arias‐Moliz, M. T.; Ferrer‐Luque, C. M.
Abstract: Aim: To evaluate the antibiofilm activity of 2.5% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 2% alexidine (ALX) and 0.2% cetrimide (CTR) alone and in combination on mature polymicrobial root canal biofilms on human dentine using confocal laser scanning microscopy (CLSM). Methodology: Twenty‐eight human dentine specimens were infected for 21 days with microbial samples collected from infected root canals of three volunteers. Antibiofilm activity of the irrigating solutions was evaluated after 3 min of contact time under CLSM. For quantification purposes, bioimage_L software was used. The variables evaluated were the log10 of total biovolume (μm 3 ) and percentage of live cells (green) population. Statistical analysis of both variables was performed using ananova test and a post hoc Duncan test to determine significant clusters amongst groups. The variable green population percentage was previously subjected to the normalized Anscombe transformation. Results: The NaOCl group had a total biovolume and percentage of live cells significantly lower than the other groups ( P ˂ 0.001). The addition of 0.2% CTR significantly increased the antimicrobial effect of 2% CHX ( P ˂ 0.001). There were no significant differences between 0.2% CTR, 2% ALX and the combination of both ( P ˂ 0.05). Conclusions: Overall, 2.5% NaOCl dissolved and killed bacteria significantly more efficiently when used against polymicrobial mature biofilm on human dentine. Cetrimide improved the antimicrobial activity of chlorhexidine and alexidine.